日の出岬におけるコケ・地衣群落の植物社会学的研究 - 小林, 圭介; コバヤシ, ケイスケ; Kobayashi, Keisuke (国立極地研究所, 2017)
第15次日本南極地域観測の一環として1973年12月30日から1974年1月6日にかけて，日の出岬の露岩地域に発達するコケ・地衣群落を植物社会学的に解明した．その結果，本論文ではA. Ceratodontetum purpurei ass. nov.: 1. Subass. of typicum, 2. Subass. of Protoblastenia citrina, 3. Subass. of Protoblastenia citrina-Rinodina olivaceobrunnea, 4. Subass. of Rinodina olivaceobrunnea, 5. Subass. of Alectoria minuscula, 6. Subass. of Alectoria minuscula-Buellia frigida, 7. Subass. of Buellia frigida; B. Buellietum frigidae ass. nov.: 8. Subass. of typicum, 9. Subass. of Caloplaca elegans var. pulvinata; C. Alectorietum minusculae ass. nov.: 10. Subass. of Buellia frigida, 11. Subass. of typicumの3新群集と11亜群集を識別し，群集組成表と分布図とともにその種組成や生態などの記載を行った．さらに，これら植生単位については，類似度の指数から相互関係を分析し，亜群集を中心とした植生単位と種組成および立地の関係を明らかにした． Under the project of the 15th Japanese Antarctic Research Expedition, the field investigation was carried out between December 30, 1973 and January 6, 1974 in Cape Hinode. This paper was undertaken to classify and describe the moss and lichen communities in Cape Hinode according to the vegetation concept and method of the Zrich-Montpellier (Z-M) school of phytosociology. The following vegetation units of moss and lichen communities were classified: A. Ceratodontetum purpurei ass. nov.: 1. Subass. of typicum, 2. Subass. of Protoblastenia citrina, 3. Subass. of Protoblastenia citrina-Rinodina olivaceobrunnea, 4. Subass. of Rinodina olivaceobrunnea, 5. Subass. of Alectoria minuscula, 6. Subass. of Alectoria minuscula-Buellia frigida, 7. Subass. of Buellia frigida; B. Buellietum frigidae ass. nov.: 8. Subass. of typicum, 9. Subass. of Caloplaca elegans var. pulvinata; C. Alectorietum minusculae ass. nov.: 10. Subass. of Buellia frigida, 11. Subass. of typicum. Each vegetation unit classified was described with an association table showing floristic composition and data on growing habitat. The distribution of each subassociation was shown on the map. The relationships among 11 classified subassociations were examined using the similarity index. departmental bulletin paper